2022
DOI: 10.1021/acs.jafc.2c06822
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydrazinoterephthalic Acid as a Novel Negative-Ion Matrix-Assisted Laser Desorption/Ionization Matrix for Qualitative and Quantitative Matrix-Assisted Laser Desorption/Ionization–Mass Spectrometry Analysis of N-Glycans in Peach Allergy Research

Abstract: Glycans recently attracted considerable attention as the proposal of cross-reactive carbohydrate determinants for food allergy. Matrix-assisted laser desorption/ionization–mass spectrometry (MALDI–MS) is powerful in analyzing biomolecules, while its applications in glycans are still challenging. Herein, a novel reactive matrix-assisted laser desorption/ionization (MALDI) matrix, 2-hydrazinoterephthalic acid, was rationally designed and synthesized. It provides uniform co-crystallization with glycans and only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Research on the use of MALDI to measure biomolecules dates back to the 1990s [13] and was awarded the Nobel Prize in 2002. Over the next 30 years, a number of variants of the technique were developed, and they are used in various biochemical analyses [14][15][16]. With the development of laser desorption-based mass spectrometry, researchers have found that the use of microarray biochips can effectively target and detect biomolecules, including DNA, RNA, peptides, sugars, proteins, etc.…”
Section: Biochip and Mass Tag-based Mass Spectrometry Sensing Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the use of MALDI to measure biomolecules dates back to the 1990s [13] and was awarded the Nobel Prize in 2002. Over the next 30 years, a number of variants of the technique were developed, and they are used in various biochemical analyses [14][15][16]. With the development of laser desorption-based mass spectrometry, researchers have found that the use of microarray biochips can effectively target and detect biomolecules, including DNA, RNA, peptides, sugars, proteins, etc.…”
Section: Biochip and Mass Tag-based Mass Spectrometry Sensing Technologymentioning
confidence: 99%
“…Bogusiewicz et al first used SPME probe MS technology for biopsy sampling of the human brain, followed by metabolic and lipidomic analysis, demonstrating higher concentrations and diversity of metabolites in the white matter [70]. Mendes et al performed direct analysis of fruit and mouse brains using inexpensive and environmentally friendly pencil graphite rods as probes for mass spectrometry biosensing [15]. Cheng et al coupled SPME with nanoESI-MS, achieved by surface-coated acupuncture needles, for the in vivo detection of small molecules, proteins, and peptides in plants [71].…”
Section: In Vivo Probe Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation